Usage behavior and health benefit perception of youth in urban parks: A case study from Qingdao, China - Yao, Wenfei; Yun, Jiayue; Zhang, Yiping; Meng, Tian; Mu, Zhiyue (Frontiers in Public Health, 2022)
With the development of urban park, people’s cognition of the relationship between the environment and public health has enhanced, which leading to more requirements regarding their living environment. As an important group of park users, young people often have different needs regarding the health benefits brought about by urban parks. In order to explore the potential relationship among young people’s satisfaction with urban parks, usage behavior and health benefit perception, this paper puts forward some constructive suggestions on the development of healthy landscape in urban parks. Researchers have selected five typical urban parks from different areas in Qingdao, China. Furthermore, we have used survey method by combining the practices of “issuing questionnaires, observing and interviewing” with the goal of collecting data on 500 park visitors in autumn, including information on social demography, satisfaction of park landscape variables, usage behavior and health perception. Linear regression model has been used to analyze the correlation among “landscape variables”, “usage behavior” and “health benefit perception”. Results have shown that urban green landscapes and waterscape can significantly affect young people’s social health perception and static behaviour. Moreover, static behaviors like relaxation have a great impact on mental health perception. The results of this study will be beneficial in understanding young people’s needs for landscapes when using urban parks. Additionally, it will provide insight for urban planners and landscape designers to design urban parks from the perspective of young people.